Effects of boron oil fortifier on friction and pressure distribution in engine journal bearings - Kaleli, H; Durak, E (EMERALD, 2003)
Additives are incorporated in engine oils to improve existing desirable properties of base stocks and to impart new specific properties required by modern engines. The additives include antioxidants, detergents, dispersants, corrosion and rust inhibitors, viscosity index improvers, pour point depressants, foam inhibitors and tribological agents. In this study, the effect of boron oil fortifier added into the base oil on friction coefficient and pressure distribution was investigated between sliding surfaces of engine journal bearings. Experiments were performed firstly using only base oil at different speeds and loads. Then, this test was repeated with different concentration ratio of 1, 3, 5 and 10 percent commercial boron additive.
Keywords: engines; friction; bearings; Engineering